USING EFFECTIVE CLASSROOM MANAGEMENT OF DIFFERENTCOUNTRIES IN LEARNING ENGLISH - Sratdinova , Gulbakhar Bakhtiyarovna; Babajanova , Ayzada Bayram kizi (Educational Research in Universal Sciences, 2022)
Our rapidly evolving educational system is aiming to successfully teach many foreign languages, mainly English. Based on the experience of the most educated countries, this article offers a few precise and highly effective methods for classroom management in English instruction.